On the influence of thickness non-uniformity on mechanical behaviour under small punch load - Pandit, Sarthok Chandra; Nasrul Azuan, Alang; Ferdous, I. U.; Juliawati, Alias; Mohd Firdaus, Hassan; Norhaida, Ab Razak (IOP Publishing, 2025)
The Small punch (SP) test is an alternative method to determine the mechanical properties of various materials, including metallic and non-metallic. It uses a relatively small amount of material as a test sample and causes minimum damage to the components during sample extraction, giving it advantages over conventional test methods. However, preparing SP samples with accurate and uniform thickness is challenging. This issue leads to inconsistency in the mechanical properties data obtained from the SP test. The present study numerically investigates the effect of non-uniform sample thickness on the displacement-force data of alloy steel under small punch load at room temperature. The thickness of the sample varies in both radial and through-thickness directions to simulate real material conditions during the laboratory sample preparation stage. This variation in thickness is modelled in Finite Element (FE) Abaqus v6.14 software, considering axis-symmetric conditions. Appropriate load, boundary conditions, and mesh design are assigned to the model. It is found that the non-uniformity of the sample in through-thickness direction affects the displacement-force behaviour of the material. Furthermore, the stress and strain distribution are also affected. The displacement-force response, however, remains constant under the effect of radial non-uniformity. Based on the study, it can be concluded that sample preparation is a critical stage which requires exceptional attention to obtain reliable results in the SP test.